(Sub)populations of extracellular vesicles released by TNF‐α –triggered human endothelial cells promote vascular inflammation and monocyte migration. Issue 1 (11th August 2020) - Hosseinkhani, Baharak; van den Akker, Nynke M.S.; Molin, Daniel G.M.; Michiels, Luc
ABSTRACT: Substantial research has been devoted to discovering the translational potential of extracellular vesicles (EV) as a reliable liquid biopsy in the diagnosis and monitoring of several life‐affecting diseases, including chronic inflammatory diseases (CID). So far, the role of EV in the development of CID remains largely unknown due to the lack of specific tools to separate the disease‐associated EV subtypes. Therefore, this study aims to fractionate inflammation‐associated EV (sub)populations using a two‐step separation strategy based on their size combined with a specific inflammatory marker (ICAM‐1) and to unravel their proteome signature and functional integrity at the onset of vascular inflammation. Here, we report that vascular endothelial cells upon inflammation release two heterogeneous size‐based populations of EV (EV‐10 K and EV‐110 K) sharing a cocktail of inflammatory proteins, chemokines, and cytokines (chiefly: ICAM‐1, CCL‐2, CCL‐4, CCL‐5, IL‐8 and CXCL‐10). The co‐enrichment of ICAM‐1 and classical EV markers within these two size‐based populations gave us a promising opportunity to further separate the inflammation‐associated EV subpopulations, using an immuno‐affinity methodology. Protein profiling of EV subpopulations highlighted that the phenotypic state of inflamed endothelial cells is preferentially mirrored in secreted medium‐ and large‐sized ICAM‐1 (+) EV. As functional players, the smaller‐sized EV and especially their ICAM‐1 (+) EV subpopulation promote the migration of THP‐1 monocytes, whereas the large ICAM‐1 (+) EV were more potent to induce ICAM‐1 expression in recipient endothelial cells. This study provides new insights into the immunomodulatory content of inflammation‐associated EV (sub)populations and their functional contributions to the initiation of vascular inflammation (ICAM‐1 expression) and monocyte mobilization.